Selective Propagation of Retinal Pericytes in Mixed Microvascular Cell Cultures Using L-Leucine-Methyl Ester. (September 1998) - Lee, C.S.; Patton, W.F.; Chung-Welch, N.; Chiang, E.T.; Spofford, K.H.; Shepro, D.
Endothelial cell (EC) propagation has been simplified by developing cell-specific selection criteria. Methods commonly used for selectively isolating EC include: (i) differential sieving of disaggregated tissue, (ii) differential plating of cells on extracellular matrices, (iii) lectin affinity isolation of cell populations and (iv) fluorescence-activated cell sorting of cells labeled with a carbocyanine dye of acetylated low-density lipoprotein (DiI-Ac-LDL). Few criteria for selectively propagating pericytes (PC) are currently available. Nonspecific esterases exhibit a high degree of multiplicity when compared with other mammalian isozymes and may be suitable for the identification and selective propagation of cells of the microvasculature. Evaluation of esterase isotype expression in PC and EC by zymography indicates PC contain α-naphthyl acetate anda-naphthyl butyrate hydrolyzing esterases as well as dipeptidyl peptidase I, while EC only containa-naphthyl acetate esterase. The cytotoxic response of PC and EC to various amino acid esters is assessed by monitoring vital dye uptake and by light microscopy. Several amino acid esters are cytotoxic to both cell types, whereas 50 mM L-leucine methyl ester (L-Leu OMe) is toxic to EC but not to PC. This amino acid ester is also toxic to mesothelial and retinal pigmented epithelial cells, other common contaminants of PC cultures. Analysis of protein composition by two-dimensional gel electrophoresis indicates that L-Leu OMe does not stimulate expression of stress response proteins in PC. Thus, L-Leu OMe can be utilized to cultivate PC selectively from mixed cell populations.